2016
DOI: 10.1213/xaa.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Noninvasive Hemodynamic Monitoring in an Infant With Tetra-Amelia

Abstract: Tetra-amelia syndrome is a congenital disorder associated with near or complete absence of all 4 limbs. Noninvasive hemodynamic monitoring may be difficult or impossible in such patients. We describe the use of a finger cuff blood pressure system for continuous noninvasive blood pressure monitoring in an infant with near-complete tetra-amelia undergoing laparoscopic gastrostomy tube placement. This case suggests the potential use of such a blood pressure monitoring system for other patients with comparable def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…3 One study reported the application of a small finger cuff that was appropriate for the patient's extremity appendage. 4 In the present case, with a regular adhesive pulse oximetry sensor on the arm stump along with a forehead pulse oximetry sensor as a backup monitor, O 2 saturation was successfully monitored. Furthermore, there are other nonextremity placements of pulse oximeter probes, which may be able to be used in this such patients such as penis, tongue, or earlobe probes.…”
Section: A S E Rep Ortmentioning
confidence: 68%
See 3 more Smart Citations
“…3 One study reported the application of a small finger cuff that was appropriate for the patient's extremity appendage. 4 In the present case, with a regular adhesive pulse oximetry sensor on the arm stump along with a forehead pulse oximetry sensor as a backup monitor, O 2 saturation was successfully monitored. Furthermore, there are other nonextremity placements of pulse oximeter probes, which may be able to be used in this such patients such as penis, tongue, or earlobe probes.…”
Section: A S E Rep Ortmentioning
confidence: 68%
“…Earlier reports of patients with more extreme limb anomalies note that neither invasive nor noninvasive blood pressure monitoring could be performed because of the complete absence of all extremities 3 . One study reported the application of a small finger cuff that was appropriate for the patient's extremity appendage 4 . In the present case, with a regular adhesive pulse oximetry sensor on the arm stump along with a forehead pulse oximetry sensor as a backup monitor, O 2 saturation was successfully monitored.…”
Section: Case Reportmentioning
confidence: 70%
See 2 more Smart Citations